Efeitos de diferentes lâminas de irrigação na cultura do rabanete - Klar, Antônio Evaldo [UNESP]; Putti, Fernando Ferrari; Gabriel Filho, Luís Roberto Almeida [UNESP]; Da Silva Junior, Josué Ferreira; Cremasco, Camila Pires [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2015)
The aim of this study was to analyze the performance of the radish crop under different levels of water replacement. The experiment was carried out at the Department of Rural Engineering, College of Agricultural Sciences - UNESP/Botucatu – SP. The experimental design was randomized blocks with five irrigation depths (25%, 50%, 75%, 100% and 125% Etc) and 10 replicates. A total of two crop cycles were conducted to analyze the crop performance. The following parameters were evaluated: number of leaves; root, bulb and above-ground green phytomass; bulb length and diameter and root length. Similar performance was observed for both cycles, characterized by a quadratic increase in irrigation depths with an optimal point from 60% to 80% Etc.
The effects of different irrigation depths on radish crops
Keywords: Efficiency; Evapotranspiration; Management; Optimization